Exploring Occupant Behavior in Buildings Methods and Challenges (Springer International Publishing, 2018)
This book is the first to comprehensively cover research methods for building occupant behavior. As this is of growing importance for building design and for building performance optimization, the book aims to provide a sound scientific basis for experimental studies in this field. It introduces the reader to fundamental questions about the topic and unfolds the different fields related to occupant actions and comfort. This is followed by more general questions about developing an appropriate research method and experimental design. A comprehensive overview of sensors for monitoring environmental and also behavioral and action-related quantities helps to set up an experiment. In this context, different experimental environments and data collection methods (in-situ, laboratories, surveys) are introduced and discussed in terms of their suitability for the respective research question. Furthermore, data management and reporting is addressed. The book concludes with fundamental challenges in conducting occupant studies, with chapters on ground truth, ethics and privacy.